Breaking Immunological Tolerance in Systemic Lupus Erythematosus - Pieterse, Elmar; van der Vlag, Johan (Frontiers in Immunology, 2014)
Systemic lupus erythematosus (SLE) is a fairly heterogeneous autoimmune disease of unknown etiology that mainly affects women in the childbearing age. SLE is a prototype type III hypersensitivity reaction in which immune complex depositions cause inflammation and tissue damage in multiple organs. Two distinct cell death pathways, apoptosis and NETosis, gained a great deal of interest among scientists, since both processes seem to be deregulated in SLE. There is growing evidence that histone modifications induced by these cell death pathways exert a central role in the induction of autoimmunity. In the current review, we discuss how abnormalities in apoptosis, NETosis, and histone modifications may lead to a break of immunological tolerance in SLE.